Population pharmacokinetic/pharmacodynamic analysis of AK111, an IL-17A monoclonal antibody, in subjects with moderate-to-severe plaque psoriasis - Qian Li; Ju Qiao; Hongzhong Jin; Benchao Chen; Zhimei He; Guoqin Wang; Xiang Ni; Max Wang; Michelle Xia; Baiyong Li; Rui Chen; Pei Hu (Frontiers Media S.A., 2022)
AK111 is an innovative IL-17A antibody, presenting high affinity to IL-17A and showing similar pharmacokinetic (PK) characteristics to those of typical immunoglobulin (Ig) G1 antibodies. To optimize the dosage regimen for phase 2/3 clinical trials, PK and pharmacodynamics (PD) of AK111 were first characterized in Chinese moderate-to-severe plaque psoriasis patients in a phase 1b study. AK111 PK serum sample and Psoriasis Area and Severity Index (PASI) score data were collected from 48 moderate-to-severe psoriasis patients in this study. Non-linear mixed-effects modeling was used for the population PK/PD analysis. A one-compartment model with a first-order absorption and a first-order elimination best described the PK behavior of AK111. The apparent systemic clearance was 0.182 L/day, and the central volume was 6.65 L. The exposure-response relationship was characterized using an indirect response model. The pharmacological effect of AK111 was described in the form of inhibiting the formation of psoriatic plaque, whereas placebo was quantified in the form of promoting the degradation of psoriatic skin lesions. The maximum effect of drug effect (Imax) and placebo effect (PLBmax) was 1 and 0.429, respectively. The rate constant for psoriatic plaque production (Kin) was 0.474 PASI/day and psoriatic plaque loss (Kout) was 0.024 day−1. The body surface area (BSA) affected by psoriasis was identified as a significant covariate on Kout. The simulation results confirmed that all of the predicted PASI90 response rates at week 12 were higher than 60% at 150 and 300 mg dose levels with different regimens and could reach higher than 80% at week 24. We hope this first PK/PD study of AK111 in Chinese moderate-to-severe plaque psoriasis patients will be of help in the further clinical development of AK111 and provide a reference to the dosage optimization for similar antibodies with a long half-life.